THE IMPLEMENTATION OF DISAGGREGATION ALGORITHM IN THE ANALYSIS OF ENERGY CONSUMPTION BASED ON THE INTERNET-OF- THINGS TECHNOLOGY - Husein H; Aditya Alviori; Maman Budiman; Mitra Djamal (AGRIBUSINESS JOURNAL, 2019)
The effort to reduce the mass energy usage without involvement of consumers is not effective. Thereby, creating a pathway for anyone of consumer to be much more involved in the energy-saving effort. The implementation of disaggregation algorithm in the analysis of energy consumption is to recognize when and which appliance has the largest energy consumption and being able to control the state of all appliances from anywhere. In this research, the principle of disaggregation is event-based and low-sampling data frequency. A KWH-meter is used to send power data to the cloud server via MQTT protocol. The cloud server gathers the energy-consumption data, analyses them and then disaggregates them. The output of the disaggregation algorithm would tell the state (on/off), the average power and the percentage of energy consumed by each appliances. The output will then be sent from the cloud server to Android Apps via MQTT protocol. Then the consumer can easily access and control the energy consumption from their smartphone after knowing it through the disaggregation algorithm.